If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(-1/6)*(y+4) = (3/8)*(y+1) // - (3/8)*(y+1)
(-1/6)*(y+4)-((3/8)*(y+1)) = 0
(-1/6)*(y+4)+(-3/8)*(y+1) = 0
-1/6*(y+4)-3/8*(y+1) = 0
-1/6*(y+4)-3/8*(y+1) = 0
-13/24*y-25/24 = 0
-13/24*y-25/24 = 0
-13/24*y-25/24 = 0 // + 25/24
-13/24*y = 25/24 // : -13/24
y = 25/24/(-13/24)
y = -25/13
y = -25/13
| -1/8*x=-3/4 | | y-13=-1(x+7) | | 6u-u=45 | | 2x^3+x^2+1=0 | | 2(x+5)=3(5+3x)-7 | | -4/7x=-1 | | 2k+3(k+1)=6k-3 | | 7y+2y=36 | | 141x-22=5 | | 5c+4=24 | | 5x+8=2x+50 | | 2x+2.1=8.9 | | 13(7z)= | | 9-5(3z-4)=-7(-3z-3)-4 | | 1/2k=40 | | 26e+891=72.46 | | 3(3v-8)=21 | | 100=-4x+2(-3x-5) | | -10-8p=-8(6p-5)+10(2+4p) | | x^2+10x-50=0 | | 6w-7=14 | | 16-2m+6=3+2m-13 | | 3y+2=2y-4 | | 3c=c | | -3.2=6.8-2y | | n=2+-2n | | 8x^2-10x+3/6x^2+3x-3 | | -3u+12=-17 | | x^(1/2)*x^(2/3) | | -3(2b-1)=4(6+5) | | 4v=2v+4 | | 2x+7=4x-2 |